Youth emancipation and perceived job insecurity of parents and children - Sascha O. Becker; Samuel Bentolila; Ana Fernandes; Andrea Ichino (Institute for the Study of Labor (IZA), 2005)
The age at which children leave the parental home differs considerably across countries. In this paper we argue that lower job insecurity of parents and higher job insecurity of children delay emancipation. We provide aggregate evidence which supports this hypothesis for 12 European countries and which helps account for the increase in coresidence in the 1990s. We also give microeconometric evidence for Italy, a country for which we have access to household-specific information on job security of fathers and coresidence. In the late 1990s, approximately 75% of young Italians aged 18 to 35 were living at home and they had only a 4% probability of emancipation in the 3 subsequent years. We show that this probability would have increased by 4 to 10 percentage points if their fathers had gone from perceiving to have a fully secure job to expecting to be unemployed for sure.
Keywords: J1; J2; 330; coresidence; youth emancipation; job security; Arbeitsplatzsicherung; Wohnstandort; Kinder; Schätzung; Italien; EU-Staaten